Memórias de mulheres do movimento estudantil: participação, gênero e educação - Silva, Mayris de Paula (Universidade Federal de São Carlos, 2016)
The present work aims to analyze the memory of women who acted in the student movement in 1990, conceiving each one of them as a historical, political and social subject. It was a main goal of this work to understand the women participation during the History in a student movement configured by a hierarchical and sexist environment in which the women’s struggle to survive inside spaces they are oppressed configure a process of reinvention of themselves. The methodology developed during this work is based on reports given to us during four interviews conducted with women that had participated in the student movement in the past. Themain themes discussed in these interviews were: Women Participation, Gender and Education. The reported memories gave visibility for the political context of the 90’s, covering from the universities to the student movement as a whole and its relation withsociety. The whole set of considerations about women actuation inside and out of the student movement given to us, were not only capable of covering questions about gender and diversity but also to show all the questions that emerge from those memories. The conclusion is that the collected testimonials from the practical and subjective experiences in the student movement came to show that the re-inventions contemporary women have been through in their daily life were somehow led by those experiences. Women participation in the public world can bring a variety of themes to public discussion, but specially values and questions that go against men’s order of things, or a sexist order of things, because when women start to understand their role in History theystart to be visible, breaking the silence of their own existence. It occurs when women are included in History.
Memories of women who acted in the student movement: women participation, gender and education
Keywords: Movimentos estudantis; Student movements; Mulheres; Women; Gênero; Gender; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO